The nature of spin trimer in Ca₃Cu₂Ni(PO₄)₄ - Ghosh, M.; Ghoshray, K. (Физика низких температур, 2012)
The nature of spin trimer and 3d spin dynamics in Ca₃Cu₂Ni(PO₄)₄ was studied using ³¹P NMR measurements.
This material is obtained replacing one of the Cu ions by a Ni ion in one dimensional spin trimer compound
Ca₃Cu₃(PO₄)₄. NMR spectrum suggests the presence of two types of magnetically inequivalent phosphorous
atoms as in the parent compound. This finding reveals the presence of only one type of trimer viz.
Cu₂–Ni–Cu₂ rather than three types viz., Cu₂–Cu₁–Cu₂, Cu₂–Cu₁–Ni and Ni–Cu₁–Ni as suggested from neutron
scattering. Hence the ground state of Ca3Cu2Ni(PO4)4 appears to be a quintet. The present finding also explains
the magnetic susceptibility behavior showing no indication of the reduction of net spin of a trimer in
Ca₃Cu₂Ni(PO₄)₄, as expected for JNi–Cu = – 0.85 meV compared to JCu–Cu = – 4.74 meV, reported from neutron
scattering. The spin lattice relaxation rate suggests that the three magnon mediated scattering process, dominant
in Ca₃Cu₃(PO₄)₄, is reduced in Ca₃Cu₂Ni(PO₄)₄.